An Analysis of Impolite Words among Makassarese Youngsters - Srirahayu Putri; Andi Syurganda; Nur Muthmainna Halim (Humanitatis : Journal of Language and Literature, 2021)
This research aims: 1) to find out impolite words found among Makassarese youngsters 2) to find out how the impolite words are conversed and exchanged among Makassarese youngsters. The research method used in this research is a qualitative descriptive method, which is used to analyze data from the research participants, namely Makassarese youngsters. The data obtained are impolite words in the conversations Makassarese youngsters, then analyzed by using Brown & Levinson's politeness theory. Based on the results of that research, it shows that in the conversations Makassarese youngsters, there are some impolite words such as sundala, kongkong, pottele, tolo, ka'bulamma and telang spoken by subjects of this research. The use of these impolite words is usually exchanged by youngsters in their local community, such as close friends, also in family or even other environments that supports the situation. The use of impolite words among Makassarese youngsters is generally practiced as an opening word or conversation, while the duration of starts from the beginning of the conversation until the end of the conversation. Keywords: Impolite Words, Youngsters, Makassarese